2018
DOI: 10.1039/c8ra00358k
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of macroporous reduced graphene oxide composite aerogels reinforced with chitosan for high bilirubin adsorption

Abstract: Chitosan reinforced macroporous reduced graphene oxide composite aerogels were fabricated with high bilirubin adsorption properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 66 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…Activated partial thromboplastin time (aPTT) and prothrombin time (PT) were used to characterize the influence of CDDs‐TBA on the intrinsic coagulation pathway and extrinsic coagulation pathway, respectively. [ 31 ] The results showed that the aPTT values were significantly reduced by 2%CDDs‐30%TBA (21.16 ± 0.99%), followed by 2%CDDs‐60%TBA (27.60 ± 1.07%), 2%CDDs (29.77 ± 1.61%), and 2%CDDs‐100%TBA (30.93 ± 0.99%) compared with that of control group (Figure 4C). Silanol group has very strong polar interactivity, [ 32 ] which exists on the surface of DB in CDDs‐TBA.…”
Section: Resultsmentioning
confidence: 96%
“…Activated partial thromboplastin time (aPTT) and prothrombin time (PT) were used to characterize the influence of CDDs‐TBA on the intrinsic coagulation pathway and extrinsic coagulation pathway, respectively. [ 31 ] The results showed that the aPTT values were significantly reduced by 2%CDDs‐30%TBA (21.16 ± 0.99%), followed by 2%CDDs‐60%TBA (27.60 ± 1.07%), 2%CDDs (29.77 ± 1.61%), and 2%CDDs‐100%TBA (30.93 ± 0.99%) compared with that of control group (Figure 4C). Silanol group has very strong polar interactivity, [ 32 ] which exists on the surface of DB in CDDs‐TBA.…”
Section: Resultsmentioning
confidence: 96%
“…The other peaks at 285.40, 286.58, and 288.84 eV are ascribed to the functional groups of C–N, C–O, and O–C=O, respectively. The arisen functional group of C–N may be due to the attachment of the GC chains [ 45 ]. Finally, Figure 4 h presents high-resolution XPS C 1s spectra of rGO-PGA.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the composite cryogel had a high adsorption capacity (458.9 mg/g) and a fast adsorption rate. In addition, the composite cryogel also had a low hemolysis ratio and negligible anti-coagulant activity that could suggest good compatibility and high capacity adsorption, making it a potential candidate for blood samples [57].…”
Section: Composite Cryogels As Versatile Tools For Biomedical Applmentioning
confidence: 99%